Acute toxicity and cholinesterase inhibition of the nematicide ethoprophos in larvae of gar Atractosteus tropicus (Semionotiformes: Lepisosteidae) - Freylan Mena Torres; Sascha Pfennig; María de Jesús Arias Andrés; Gabriel Márquez-Couturie; Adrían Sevilla; C. Maurizio Protti Q (Revista de Biología Tropical, 2012)
Biomarkers are a widely applied approach in environmental studies. Analyses of cholinesterase (ChE), glutathione S-transferase (GST) and lipid peroxidation (LPO) are biomarkers that can provide information regarding early effects of pollutants at different biochemical levels on an organism. The aim of this study was to evaluate the biomarker approach on a Costa Rican native and relevant species. For this, larvae of gar (Atractosteus tropicus) were exposed to the organophosphorus nematicide, ethoprophos. Acute (96hr) exposure was conducted with pesticide concentrations ranging from 0.1μg/L to 1 500μg/L. The 96hr LC50 calculated was 859.7μg/L. After exposure, three biomarkers (ChE, GST and LPO) were analyzed in fish that survived the acute test. The lowest observed effect concentration (LOEC) regarding ChE activity inhibition was 50μg/L. This concentration produced a significant inhibition (p<0.05) of the enzyme by 20%. The highest concentration tested without showing any effect on ChE activity and therefore considered as no observed effect concentration (NOEC) was 10μg/L. Ethoprophos concentration of 400μg/L caused a ChE inhibition by 79%. In this study, no significant variations (p>0.05) in GST activity and LPO were observed in A. tropicus larvae after exposure to ethoprophos.